Cofilin-actin rods: quantification and comparison to tau pathology in a human longitudinal aging study and developing probes to measure localization and activity of NADPH oxidase 2, a component of the prion-dependent rod inducing pathway - Carlson, Adlei B., author; Bamburg, James R., advisor; Di Pietro, Santiago, committee member; Amberg, Gregory C., committee member (Colorado State University. Libraries, 2015)
The presence of extracellular amyloid plaques composed mainly of fibrils of the β-amyloid peptide (Aβ) as well as intracellular neurofibrillary tangles composed mainly of hyperphosphorylated tau protein, are used for post-mortem confirmation of the diagnosis of Alzheimer's disease (AD). However, a shift in disease hypothesis has changed over the years. It is now generally accepted that soluble forms of Aβ oligomers and not fibrils, which are deposited in plaques, are most responsible for the synaptic loss and eventual neuronal death that accompanies AD progression. In cultured mammalian neurons, treatment with this more relevant, soluble form of Aβ induces the formation of cofilin-actin rods within neurons. Rods may grow to occlude the neurite and block transport, leading to loss of microtubules and synapses. Tau is a microtubule binding protein whose hyperphosphorylation depends upon its release from microtubules. Thus, rod formation might play a role in the loss of synapses and the development of tau pathology in AD. To determine if cofilin-actin rods might play a role in AD progression, we obtained samples of frontal cortex and the hippocampal formation from nearly identical regions of multiple subjects who were part of a longitudinal study and thus could be grouped as non-cognitively impaired (NCI), early AD (eAD), or mid to late AD. All samples were obtained with a short postmortem interval and the average age of subjects in each group was between 86 and 91 years. We prepared 30 μm sections of cortical and hippocampal tissue, and following immunofluorescence staining for cofilin and phosphorylated tau protein, quantified rod and neuropil thread areas in brain sections from each subject. Rods in the hippocampal formation were most prevalent in the entorhinal cortex, the first brain region to show pathology during development of AD. Comparison of rod and neuropil thread pathology in the frontal cortex revealed a correlation of neuropil thread pathology with disease transition. However, there was no correlation between rod density and disease transition, while the cortical sections revealed a surprisingly high deposition of cofilin rod pathology across all subject cohorts. This may suggest that rods play a different role within brain cortical regions than what was observed in the hippocampus. Additionally, recent work has revealed the implication of a prion-dependent rod inducing pathway dependent on the activation of the reactive oxygen producing NADPH oxidase 2 (NOX). If prion-protein density is responsible for whether a rod forms, can we investigate the NOX intensity and duration of activity in relation to where rods form in a neurite? For future study we sought to develop the sensitive NOX probes, p47-roGFP and NOX-2-redtrack. These probes will give us new tools to analyze the effects that NOX activity and expression have on rod formation. The adenoviral constructs for expression of these two probes have been made and characterized within mammalian cell lines. Evidence presented here provides the basis for the use of these probes to analyze NOX activity as it relates to the generation of rods within neurites.
Keywords: cofilin-actin rods; longitudinal ageing study; neurodegenerative disease; Alzheimer's disease